2005
DOI: 10.1242/jeb.01605
|View full text |Cite
|
Sign up to set email alerts
|

The role of myostatin and the calcineurin-signalling pathway in regulating muscle mass in response to exercise training in the rainbow troutOncorhynchus mykissWalbaum

Abstract: SUMMARY Rainbow trout Oncorhynchus mykiss Walbaum were exercised at 0.8 and 1.6 body lengths s-1 for 18 h a day over a 30 day period. Exercise resulted in a 24-30% increase in the average cross-sectional area of fast muscle fibres relative to tank-rested controls. The concentrations of growth factors and transcription factors hypothesised to play a role in regulating exercise-induced muscle fibre hypertrophy were measured. Exercise training resulted in a minor increase in calcineurin localisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…The latter event is thought to synergistically initiate a programme of gene expression leading to fibre hypertrophy (Musaro et al, 1999;Semsarian et al, 1999). However, exercise training leading to fast muscle hypertrophy in the rainbow trout only resulted in a minor increase in calcineurin localisation in the nucleus and total NFAT2 concentration decreased relative to tank-rested controls with no nuclear translocation (Martin and Johnston, 2005). These results indicate differences in the response of this signalling pathway to exercise stimuli between teleosts and mammals.…”
Section: Myogenesis and Exercisementioning
confidence: 88%
“…The latter event is thought to synergistically initiate a programme of gene expression leading to fibre hypertrophy (Musaro et al, 1999;Semsarian et al, 1999). However, exercise training leading to fast muscle hypertrophy in the rainbow trout only resulted in a minor increase in calcineurin localisation in the nucleus and total NFAT2 concentration decreased relative to tank-rested controls with no nuclear translocation (Martin and Johnston, 2005). These results indicate differences in the response of this signalling pathway to exercise stimuli between teleosts and mammals.…”
Section: Myogenesis and Exercisementioning
confidence: 88%
“…In other mammalian studies, muscle myostatin expression has paradoxically increased in response to training or overloading in skeletal or cardiac muscle (Sakuma et al, 2000;Willoughby, 2004;Matsakas et al, 2006;Jensky et al, 2007;Jensky et al, 2010). In rainbow trout (Oncorhynchus mykiss), Martin and Johnston found a significant decrease in myostatin protein in response to training, but the magnitude of the decrease was so small (6%) that they concluded myostatin played no more than a minor role in regulating muscle mass after exercise (Martin and Johnston, 2005). Our results from starlings exercising in a wind tunnel demonstrate traininginduced muscle hypertrophy, yet no decrease in myostatin mRNA expression in response to either acute exercise or 2 weeks of flight training; in fact, myostatin mRNA expression trended higher immediately after a long-duration flight compared with trained and untrained animals.…”
Section: Exercise and The Expression Of Myostatin Tll1 And Igf1 Mrnamentioning
confidence: 98%
“…Resistance training and endurance exercise can result in increased muscle size as muscles acclimate to increased workload (Roth et al, 2003;Walker et al, 2004;Willoughby, 2004;Martin and Johnston, 2005). Exercise and training have also been associated with decreased expression of myostatin mRNA and protein in humans (Roth et al, 2003;Raue et al, 2006;Louis et al, 2007) and rats (Matsakas et al, 2005;Matsakas et al, 2006;Heinemeier et al, 2007), although this finding has not been consistent.…”
Section: Exercise and The Expression Of Myostatin Tll1 And Igf1 Mrnamentioning
confidence: 99%
“…have been extensively studied (Johnston & Moon 1980, Martin & Johnston 2005, He et al 2013. Some studies have found that the im provement of U crit was accompanied by the enhancement of aerobic metabolic capacity in trained fish (Liu et al 2009, Li et al 2010b.…”
Section: Effect On Swimming Efficiencymentioning
confidence: 99%